2016
DOI: 10.1037/neu0000232
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and the contribution of short-term memory span in children with specific language impairment.

Abstract: Objective: An increasing number of results show that specific language impairment (SLI) is often associated with impairments in executive functions (EF), but the nature, extent, and generality of these deficits is yet unclear. The aim of the paper is to present results from verbal and nonverbal tasks examining EF in children with SLI and their age-matched typically developing (TD) peers. Method: 31 children with SLI were tested on verbal and nonverbal versions of simple and complex span, fluency, N-back, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 48 publications
3
57
2
2
Order By: Relevance
“…This domain‐general hypothesis presumes that under high‐demand conditions, the executive system draws resources from the phonological system, the visual‐spatial system or the general system (i.e., the long‐term memory, see Baddeley & Logie, ). In line with the domain‐general hypothesis, more general working memory deficits become evident in language‐disordered children (Lukács, Ladányi, Fazekas, & Kemény, ; Vugs, Cuperus, Hendriks, & Verhoeven, ).…”
Section: Introductionmentioning
confidence: 70%
“…This domain‐general hypothesis presumes that under high‐demand conditions, the executive system draws resources from the phonological system, the visual‐spatial system or the general system (i.e., the long‐term memory, see Baddeley & Logie, ). In line with the domain‐general hypothesis, more general working memory deficits become evident in language‐disordered children (Lukács, Ladányi, Fazekas, & Kemény, ; Vugs, Cuperus, Hendriks, & Verhoeven, ).…”
Section: Introductionmentioning
confidence: 70%
“…The choice of predictors in the third step was determined a priori based on findings in previous literature showing that fluid intelligence and verbal shortterm memory impact vocabulary development (Baddeley, 2003;Paradis, 2011) and are related to executive function (Friedman et al, 2006;Lukács, Ladányi, Fazekas, & Kemény, 2016). For similar reasons, the child-external factor, parental education, was added (Ardilla, Rosselli, Matute, & Guajardo, 2010;Hoff, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown inconsistent results regarding inhibition deficits in children with DLD. Some studies (Bishop & Norbury, 2005;Ebert & Kohnert, 2011;Finneran, Francis, & Leonard, 2009;Henry et al, 2011;Pauls & Archibald, 2016;Spaulding, 2010) pointed out difficulties in children with DLD compared to their typically developing (TD) peers, whereas other studies (Hanson & Montgomery, 2002;Lukács et al, 2016;Marton et al, 2012;Noterdaeme et al, 2001) did not demonstrate differences between these groups. This divergence could be due to the various tasks used to measure inhibition (Pauls & Archibald, 2016).…”
Section: Executive Functions In Children With Dldmentioning
confidence: 99%